La poétique de la réécriture chez Gaston Miron - Beaudet, Marie-Andrée (Romanica Silesiana)
Few writers have done as much rewriting as the Québécois poet Gaston Miron. The poems collected in his masterwork “L’homme rapaillé”, first published in 1970, have been subjected to a long process of rewriting from the end of the 1940’s to his death in 1996. As Miro himself claimed, the last edition of “L’homme rapaillé”, published in 1993, was “non definitive” and numerous verses were still considered unfinished (“vers en souffrance”). The article examines this peculiar poetics of rewriting in order to explain the reasons and the circumstances that kept bringing Miron back to his poems, while his work was enthusiastically received by readers and critics alike. Key words : Gaston Miron; poetry; rewriting